Postoperative scar deformities of the perianal region: current state of the problem. (literature review) - Aksan Mуkhailo (The Ukrainian Scientific Medical Youth Journal, 2022)
Nowadays, many surgical interventions are performed in the perianal area and on the anal canal. Each one affects the quality of the patient’s future life in its own way. That is why the presented literature review is devoted to the study of the problem of postoperative scar deformities of the perianal region, because this pathology is a complication of many surgical interventions in this area. The main objective of the study is to analyze the currently available data in the following areas: the cause of postoperative scar deformities, their classification and modern treatment methods. The research method was based on the study of scientific articles published in the period from 1982 to 2022, indexed in Ukraine and international databases. This approach made it possible to identify key points in each of the areas of analysis and to systematize the obtained data. When studying the causes of postoperative anal stenosis, it can be noted that most often they represent the consequences of hemorrhoidectomies, performed in various techniques. Most scientists emphasize the importance of preventing the occurrence of anal stenosis, which implies choosing the optimal treatment method. Having systematized the literature data, I would like to note the lack of a unified approach to managing patients with this problem, as well as the lack of well-defined indications for surgical treatment. The vast majority of researchers emphasize the need to treat these patients using conservative methods, namely dietary adjustments. Regarding the methods of surgical treatment, it is necessary to note the vast quantity of available surgical techniques. At the same time, the lack of controlled prospective studies makes it difficult to evaluate and verify their results. However, it is indisputable that all of them lead to an improvement in the lives of patients and a reduction in the symptoms of stenosis. After analyzing a sufficient amount of available data, it is safe to say that the issue of postoperative scar deformities of the perianal region remains insufficiently studied and very relevant.